Dampak Pengangguran Terhadap Kemiskinan - Romualdus Turu Putra; Agusto agusto agusto (Faculty Of Economics and Business, Musamus University, 2023)
A study to determine the level of net income of rice mill entrepreneurs and to determine the efficiency level of rice mill entrepreneurs in Waninggap Miraf Village Merauke. opulation in this study was 25 people and the samples taken in the study were 25 people Data was collected through questionnaires and interviews. The data analysis tool used to determine the level of income is profitability analysis: =RT-TC. The results showed that all rice mill entrepreneurs did not get a loss, this was because all rice mill entrepreneurs had production costs that were issued and they earned a large enough income or income so that they made a profit.